ANALISIS YURIDIS LARANGAN MEROKOK BAGI PENGEMUDI SEPEDA MOTOR DI JALAN RAYA - Fahririn, Fahririn; Al Hakim, M. Lu’ay (Yayasan Merassa Indonesia Publikasi, 2023)
Traffic safety aims to reduce victims of traffic accidents on the road. The number of victims of traffic accidents is much higher than that of sea, rail, and air transport accidents. Every regulation made is aimed not to